1994
DOI: 10.1002/eji.1830240524
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 controls interferon‐γ and tumor necrosis factor production during experimental endotoxemia

Abstract: Interleukin-10 (IL-10) is a potent inhibitor of lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF) production and has been shown to protect mice from endotoxin shock. As IFN-gamma is another important mediator of LPS toxicity, we studied the effects of IL-10 on LPS-induced IFN-gamma synthesis in vitro and in vivo. First, we found that the addition of recombinant human IL-10 (rhIL-10) (10 U/ml) to human whole blood markedly suppressed LPS-induced IFN-gamma release while neutralization of endogenously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
165
1
7

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(187 citation statements)
references
References 27 publications
(6 reference statements)
14
165
1
7
Order By: Relevance
“…This hypothesis was tested by injecting mice with neutralizing anti-IL-10 MoAb (JES5-2A5, 2 mg) before MPDS (50 mg/kg) and LPS administration. As previously reported, no immunoreactive IL-10 could be detected in the serum of anti-IL-10-treated mice ( [18] and data not shown). Figure 3 shows that neutralization of endogenous IL-10 up-regulated TNF production in mice injected with LPS with or without MPDS (hatched bars).…”
Section: Il-10-independent Mechanisms Mediate Most Of the Inhibitory supporting
confidence: 84%
See 2 more Smart Citations
“…This hypothesis was tested by injecting mice with neutralizing anti-IL-10 MoAb (JES5-2A5, 2 mg) before MPDS (50 mg/kg) and LPS administration. As previously reported, no immunoreactive IL-10 could be detected in the serum of anti-IL-10-treated mice ( [18] and data not shown). Figure 3 shows that neutralization of endogenous IL-10 up-regulated TNF production in mice injected with LPS with or without MPDS (hatched bars).…”
Section: Il-10-independent Mechanisms Mediate Most Of the Inhibitory supporting
confidence: 84%
“…As previously described [18], injection of 100 g LPS into mice resulted in the rapid release of TNF (Fig. 1a) and IL-10 ( Fig.…”
Section: High Dose Mpds Increases Lps-induced Il-10 Release In Vivo Isupporting
confidence: 66%
See 1 more Smart Citation
“…The role of IL-10 in experimental sepsis remains controversial. The exogenous application of IL-10 can prevent septic shock in mice by inhibiting the synthesis of proinflammatory cytokines, while neutralizing IL-10 inhibited bacterial outgrowth in lungs and improved survival during murine pneumonitis [23,24]. Furthermore, recent studies demonstrated that sepsis is characterized by a biphasic immunological response: an initial hyperinflammatory phase, followed by a hypoinflammatory phase [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, IL-10 is produced by monocytes and macrophages following exposure to LPS [9], and its mechanism of action includes down-regulating the production of pro-inflammatory cytokines such as IFN-c, as well as repressing IFN-c-mediated signal transducer and activator of transcription (STAT)-1 activation through induction of the suppressor of cytokine signaling family of proteins [12]. The importance of IL-10 in controlling proinflammatory cytokine release is evidenced by studies demonstrating increased mortality among mice with neutralized or deficient IL-10 following LPS challenge [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%